1993
DOI: 10.1007/bf01351842
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclastic resorption of Ca-P biomaterials implanted in rabbit bone

Abstract: The nature of the multinucleated cells involved in the resorption processes occurring inside macroporous calcium-phosphate biomaterials grafted into rabbit bone was studied using light microscopy, histomorphometric analysis, enzymatic detection of tartrate-resistant acid phosphatase (TRAP) activity, scanning, and electron microscopy. Samples were taken at days 7, 14, and 21 after implantation. As early as day 7, osteogenesis and resorption were observed at the surface of the biomaterials, inside the macropores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 37 publications
4
46
0
Order By: Relevance
“…During this period, the ceramic degraded by a disso- lution-precipitation process, as previously demonstrated by high-resolution transmission electron microscopy (TEM). 21,37,41,45 The dissolution and reprecipitation of biological apatite occurs inside the micropores of the MBCP ceramic. The first cells to arrive-macrophages-are rapidly replaced by osteoblasts and osteoclasts, which produce and remodel bone in the ceramic implant.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, the ceramic degraded by a disso- lution-precipitation process, as previously demonstrated by high-resolution transmission electron microscopy (TEM). 21,37,41,45 The dissolution and reprecipitation of biological apatite occurs inside the micropores of the MBCP ceramic. The first cells to arrive-macrophages-are rapidly replaced by osteoblasts and osteoclasts, which produce and remodel bone in the ceramic implant.…”
Section: Discussionmentioning
confidence: 99%
“…Because surface reactivity and physical topography can both influence osteoblast differentiation but are linked to surface architecture, it is currently unknown which, if either, material property plays a prevailing role in osteoinduction (Curran et al, 2006;Habibovic et al, 2006a;Vlacic-Zischke et al, 2011;Zhao et al, 2007). Alternatively, osteoinduction may depend on (pre-) osteoclast activity for osteogenic signals rather than intrinsic physicochemical signals originating from the material itself (Baslé et al, 1993;Gauthier et al, 2005;Malard et al, 1999). In support of this theory, it has been reported that osteoclastogenesis precedes osteoinduction by microstructured TCP by several weeks (Akiyama et al, 2011;Kondo et al, 2006), and osteoclast depletion limits (Ripamonti et al, 2010) or completely blocks de novo bone formation by osteoinductive CaPs (Davison et al, 2014a).…”
Section: Nl Davison Et Al Osteoinduction and Osteoclastogenesis By Bmentioning
confidence: 99%
“…Intensive efforts have been made to determine the most adequate composition and architecture. On the chemical side, many materials varying in composition and architecture have been proposed, including polymers (Ishaug-Riley et al, 1997;Ignatius et al, 2001;Mondrinos et al, 2006;Gogolewski et al, 2008), metals (Ayers et al, 1999;Bobyn et al, 1999;Itala et al, 2001;Witte et al, 2007) and ceramics (Klawitter and Hulbert, 1971;Klein et al, 1985;van Blitterswijk et al, 1986;Eggli et al, 1988;Daculsi and Passuti, 1990;Schliephake et al, 1991;Basle et al, 1993;Metsger et al, 1993;Lu et al, 1999;Flautre et al, 2001;Walsh et al, 2003;Jones and Hench, 2004;Linhart et al, 2004;Hench, 2006;Von Doernberg et al, 2006;Lan Levengood et al, 2010;Murakami et al, 2010;Yuan et al, 2010;Polak et al, 2011;Haugen et al, 2013). These materials present very different resorption rates, and many resorption mechanisms, such as dissolution, hydrolysis (e.g., poly(α-hydroxy acids) (Ignatius et al, 2001)), cell-mediated resorption (Basle et al, 1993;Lu et al, 1999;Von Doernberg et al, 2006;Yuan et al, 2010), corrosion (Witte et al, 2007), enzymatic degradation (Hutmacher, 2000;Vert, 2007), and transport <...>…”
Section: Introductionmentioning
confidence: 99%